THE EFFECT OF USING PILATES EXERCISES ON SOME PHYSICAL VARIABLES AND THE LEVEL OF SKILL PERFORMANCE ON THE PARALLEL BAR - Lecturer. Dr. Ali Hussein Ali Al-Saadawi; Asmaa Sattar Khudhair (Scholars Digest Publishing, 2024)
The success of the performance requires the development of unique necessary physical qualities that contribute to its ideal performance. The special physical attributes do not appear separately when performing the skillful game performances, as this contributes to developing the type and nature of the work required in Pilates movements. Pilates movements are considered one of the modern methods widespread in the sports field, which aims to develop muscular strength and the ability to control performance through the various muscles of the body in general and the trunk muscles in particular through coordination and accuracy between both nervous systems.
Keywords: Pilates exercises- physical variables - skill performance